A naphthalimide-based fluorescent sensor for halogenated solvents. Issue 10 (21st December 2015) - Dai, Li; Wu, Di; Qiao, Qinglong; Yin, Wenting; Yin, Jun; Xu, Zhaochao
Abstract : AMN is the first sensor to have the ability to differentiate CCl4, CHCl3, CH2 Cl2 and CHBr3 from halogenated solvents. Abstract : A fluorescent sensor for halogenated solvents termedAMN is reported.AMN shows strong fluorescence in most halogenated solvents (QE > 0.1) but weak fluorescence (QE<0.01) in most non-halogenated solvents. In chlorinated solvents, the fluorescence intensity decreased with the reduction of chlorine content. On the contrary, in brominated solvents the fluorescence intensity increased with the reduction of bromine content. It is worth mentioning thatAMN displayed fluorescence emission centered at 520 nm in CCl4 with a quantum yield of 0.607, at 556 nm in CHCl3 with a quantum yield of 0.318, at 584 nm in CH2 Cl2 with a quantum yield of 0.128, whereas in CHBr3 was centered at 441 nm with a quantum yield of 0.012.AMN was shown to have the ability to differentiate CCl4, CHCl3, CH2 Cl2 and CHBr3 halogenated solvents.